Analysis of Labor Market Indicators in the Northern Great Plain Region in 2018 and 2022 - Csástyu, Lilla (International Journal of Engineering and Management Sciences, 2024)
In my study, I analyze the labor market indicators of the North Great Plain statistical region for the years 2018 and 2022 in order to map the regional labour market characteristics based on the indicators. One method of the analysis is the Beveridge curve. This complex analysis method graphically illustrates the evolution of the relationship between the unemployment rate and the proportion of vacant positions typical of the region under investigation. The results of the analysis can draw attention to possible problems in the labour market in the region. I examine the secondary statistical data in parallel with the available related literature.